2015
DOI: 10.1590/s1677-5538.ibju.2014.0134
|View full text |Cite
|
Sign up to set email alerts
|

Should oncological cases of upper urinary system be excluded at the beginning of the laparoscopic learning curve?

Abstract: Purpose:The place of oncological cases of upper urinary system in the laparoscopic learning curve was investigated.Materials and Methods:A total of 139 patients from two different centers underwent laparoscopic operations and were included in this retrospective study.Results:Mean operative times for oncological, and non-oncological cases were 101.3 (range 60-450), and 102.7 (45-490) minutes respectively. Fourty-two (31.3 %) patients were oncological cases. In 4 oncological cases, the surgeons switched to open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The conclusion was that laparoscopy can be performed at the beginning of the learning curve for such cases. It has been emphasized that very difficult procedures such as radical cystectomy and radical prostatectomy should be performed by a surgeon who has reached a certain level of experience [2]. In our study, when we compared the results of the patient with radical nephrectomy with those of other non-oncologic patients, we observed similar results in terms of the duration of operations, hospital stays and complications.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The conclusion was that laparoscopy can be performed at the beginning of the learning curve for such cases. It has been emphasized that very difficult procedures such as radical cystectomy and radical prostatectomy should be performed by a surgeon who has reached a certain level of experience [2]. In our study, when we compared the results of the patient with radical nephrectomy with those of other non-oncologic patients, we observed similar results in terms of the duration of operations, hospital stays and complications.…”
Section: Resultssupporting
confidence: 64%
“…Laparoscopic technique is a minimally invasive approach used in many surgical operations. There is a tendency toward laparoscopic surgery because it provides for shorter hospital stays, has better cosmetic results, allows patients to return more quickly to their daily lives, has a lower morbidity, reduces blood loss and postoperative pain, and its treatment results are as effective and safe as open surgery [1,2]. After transperitoneal laparoscopic nephrectomy was first performed by Clayman et al, a historical turning point in laparoscopy, laparoscopy has become the gold standard and the number of procedures has increased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes of the study tabulated in 7,12,13,[10][11][12][13] By Clayman and Gill, the fundamental surgical procedure for laparoscopic nephrectomy has been thoroughly documented. 3,14,15 Our analysis revealed that more cases included the right side, with a frequency of 29 (72.5%) cases, compared to 11 (27.5%) cases where the left side was involved. These findings were consistent with prior studies in that the right side was more frequently observed than the left.…”
Section: Laparoscopic Nephrectomymentioning
confidence: 70%